Multi-objective tasks scheduling using artificial bee colony algorithm based on cellular automata in cloud computing environment - Mehdi Salehi Babadi; Mohammad Ebrahim Shiri; Mohammad Reza Moazami Goudarzi; Hamid Haj Seyyed Javadi (International Journal of Electrical and Computer Engineering (IJECE), 2022)
Due to the development of communication device technology and the need to use up-to-date infrastructure ready to respond quickly and in a timely manner to computational needs, the competition for the use of processing resources is increasing nowadays. The scheduling tasks in the cloud computing environment have been remained a challenge to access a quick and efficient solution. In this paper, the aim is to present a new tactic for allocating the available processing resources based on the artificial bee colony (ABC) algorithm and cellular automata for solving the task scheduling problem in the cloud computing network. The results show the performance of the proposed method is better than its counterparts.